2018
DOI: 10.1259/bjr.20180008
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the therapeutic index of radiation therapy by normal tissue protection

Abstract: Normal tissue damages induced by radiation therapy remain dose-limiting factors in radiation oncology and this is still true despite recent advances in treatment planning and delivery of image-guided radiation therapy. Additionally, as the number of long-term cancer survivors increases, unacceptable complications emerge and dramatically reduce the patients' quality of life. This means that patients and clinicians expect discovery of new options for the therapeutic management of radiation-induced complications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 149 publications
(122 reference statements)
0
42
0
Order By: Relevance
“…Consequently, there is a need for novel RT strategies that maintain the anti-tumor effect whilst limiting the extent of toxicities induced in the surrounding healthy tissue. Limiting the induction of toxicities to normal tissue would subsequently increase the therapeutic index of RT regimes (7). A number of recent studies have demonstrated that irradiation at ultra-high dose rates (FLASH) diminishes the severity of toxicities in normal tissues compared to irradiation at the conventional dose rates (CONV) currently used in clinical practice (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a need for novel RT strategies that maintain the anti-tumor effect whilst limiting the extent of toxicities induced in the surrounding healthy tissue. Limiting the induction of toxicities to normal tissue would subsequently increase the therapeutic index of RT regimes (7). A number of recent studies have demonstrated that irradiation at ultra-high dose rates (FLASH) diminishes the severity of toxicities in normal tissues compared to irradiation at the conventional dose rates (CONV) currently used in clinical practice (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies over the past several decades have investigated the pathophysiological and molecular mechanisms underlying RT's effects on tumors and normal tissue. [5][6][7] Although several pharmacological approaches that prevent and mitigate radiation injury in normal tissues have been examined in preclinical studies, only a few have progressed to clinical use. 5 5-aminolevulinic acid (ALA) is widely used to induce protoporphyrin IX (PPIX), a photosensitizer used in photodynamic diagnosis and therapy for non-muscle invasive bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Although several pharmacological approaches that prevent and mitigate radiation injury in normal tissues have been examined in preclinical studies, only a few have progressed to clinical use. 5 5-aminolevulinic acid (ALA) is widely used to induce protoporphyrin IX (PPIX), a photosensitizer used in photodynamic diagnosis and therapy for non-muscle invasive bladder cancer. 8,9 ALA is distributed ubiquitously in mammalian cells and is a precursor of tetrapyrole compounds such as heme, which is essential in aerobic energy metabolism and the electron transport system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, photons lose their energy exponentially, with higher values at the entry point and lower values at the deep-seated tissues [12][13][14]. Additionally, the rising number of particle therapy centers worldwide facilitates the use of protons or heavy ions in the clinical care of cancer patients and allows the validation of the suspected superiority of particle beams compared to photon beams in terms of normal tissue protection [15,16].…”
Section: Introductionmentioning
confidence: 99%